Finite element and theoretical investigations on PVC–CFRP confined concrete columns under axial compression - Isleem, Haytham F.; Jagadesh, P.; Qaidi, Shaker; Althoey, Fadi; Rahmawati, Cut; Najm, Hadee Mohammed; Sabri, Mohanad Muayad Sabri (Frontiers in Materials, 2022)
This article examined the performance of Carbon Fiber Reinforced Polymer (CFRP) on Concrete Filled with Polymer Vinyl Chloride Tube (CFPT) columns under axial compression. Firstly, 44 CFPT specimens from the literature were analyzed using ABAQUS software to understand the compressive behavior of specimens under applied displacement. Secondly, 268 CFPT specimens are simulated to understand the influence of Carbon Fibre Reinforced Polymer (CFRP) on these control specimens with a varying number of FRP layers and wrapping depth. Other variables such as the unconfined concrete strength, the thickness of the PVC tube, and the size and slenderness ratio of the columns were also studied. Studies are extended to confinement damage plasticity model analysis of CFRP-CFPT (CCFPT) columns. Relationships between the load-carrying capacity of CCFPT columns and the CFRP properties were developed. The effect of these parameters on the CFPT leads to the development of analytical models. It is an advantage to apply a such new type of composite columns in various applications.